2020
DOI: 10.21203/rs.3.rs-15208/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum concentration of asprosin in new-onset type 2 diabetes

Abstract: Background: Asprosin, a newly identified adipokine, is pathologically increased in individuals with insulin resistance. However, the available evidence on the association of asprosin and type 2 diabetes mellitus (T2DM) status is still scarce. Therefore, this study aimed to determine the relationship between serum concentrations of asprosin and T2DM status. Methods: This observational study was performed based on 194 adults (97 newly diagnosed T2DM and 97 healthy individuals). Anthropometric and biochemical var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Romere et al first demonstrated elevated plasma asprosin levels in humans and mice with IR, increased levels of glucose and 2h-insulin in fast mice undergoing continuous or pulsatile overexpression of asprosin, and a significant decrease in glucose and insulin levels, secondary to reduced hepatic glucose release, after immunologic or genetic asprosin action inhibition (4). Several studies have shown higher serum asprosin levels in subjects with IR and/or T2DM and a correlation between these pathological conditions and asprosin serum levels (8)(9)(10)(12)(13)(14). Wang et al documented higher plasma asprosin levels in IGR (including IFG and IGT subjects) and newly diagnosed T2DM patients compared to subjects with normal glucose regulation (NGR), showing a significant positive correlation between asprosin and HOMA-IR and a negative correlation between asprosin and HOMA-B (10).…”
Section: Discussionmentioning
confidence: 99%
“…Romere et al first demonstrated elevated plasma asprosin levels in humans and mice with IR, increased levels of glucose and 2h-insulin in fast mice undergoing continuous or pulsatile overexpression of asprosin, and a significant decrease in glucose and insulin levels, secondary to reduced hepatic glucose release, after immunologic or genetic asprosin action inhibition (4). Several studies have shown higher serum asprosin levels in subjects with IR and/or T2DM and a correlation between these pathological conditions and asprosin serum levels (8)(9)(10)(12)(13)(14). Wang et al documented higher plasma asprosin levels in IGR (including IFG and IGT subjects) and newly diagnosed T2DM patients compared to subjects with normal glucose regulation (NGR), showing a significant positive correlation between asprosin and HOMA-IR and a negative correlation between asprosin and HOMA-B (10).…”
Section: Discussionmentioning
confidence: 99%
“…Asprosin deficiency may lead to loss of appetite and extreme leanness. [22] Diminished asprosin activity or asprosin depletion could be an innovative therapeutic modality for the treatment of T2DM and obesity, thus a potential target for diabetes treatment. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher circulating asprosin levels have also been noted in patients with newly diagnosed T2DM compared to healthy controls, with significant positive correlations to BMI, the homeostatic model assessment of insulin resistance (HOMA-IR) and both fasting blood glucose and triglyceride levels [44]. In addition, plasma asprosin concentrations appear to be even higher in patients with impaired glucose regulation (IGT) compared to patients with newly diagnosed T2DM [45].…”
Section: Asprosin In T2dmmentioning
confidence: 99%